2005
DOI: 10.4103/1319-3767.33318
|View full text |Cite
|
Sign up to set email alerts
|

-------------Gastric malignancy : Clinicopathologic spectrum and relationship to helicobacter pylori infection

Abstract: The study demonstrates the comparatively high frequency of gastric lymphoma in this population and confirms the intimate association of H-pylori infection to both gastric adenocarcinoma and MALT-lymphoma. Gastric lymphoma should always be considered in the differential diagnosis of gastric malignancy and the use of immunohistochemistry is essential for the differential diagnosis of some of these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
8
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
6
8
1
Order By: Relevance
“…For example, in Japan it was 61 years [8], in Pakistan 48 ± 4.47 years, and in Saudi Arabia 47 years. In our study, the median age was 55 ± 11.53 years, which was near similar to the study done in South India (54.13 ± 12.53 years) and in Mizoram (male 58 and female 57 years), and male : female ratio was 2.7 : 1, where as in Mizoram, it was 2.3 : 1, [9], in Kashmir 3.3 : 1, in Saudi Arabia 2.2 : 1 [10], and in Pakistan 1.5 : 1 [11]. …”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…For example, in Japan it was 61 years [8], in Pakistan 48 ± 4.47 years, and in Saudi Arabia 47 years. In our study, the median age was 55 ± 11.53 years, which was near similar to the study done in South India (54.13 ± 12.53 years) and in Mizoram (male 58 and female 57 years), and male : female ratio was 2.7 : 1, where as in Mizoram, it was 2.3 : 1, [9], in Kashmir 3.3 : 1, in Saudi Arabia 2.2 : 1 [10], and in Pakistan 1.5 : 1 [11]. …”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, Qurieshi et al showed 38.2% poorly differentiated adenocarcinoma and 60% moderately differentiated adenocarcinoma [13]. In contrary to the Saudi study [10], our study showed that intestinal, diffuse, and indeterminate subtypes were 53.6%, 31.1%, and 15.1%, respectively, which was near identical to the study done by Kabir et al, in which intestinal, diffuse, and indeterminate type were 52%, 28%, and 20%, respectively [12]. In our study, intestinal type and indeterminate type were significantly predominant in antral mucosa (61.3% and 57.1%, resp.)…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…23,24 Satti MB et al also showed the majority of carcinoma occurred in the antrum (60%). 25 A recent study from the southern state of Kerala in India showed that carcinoma of the distal stomach has remained predominant although a trend towards a proximal shift has been noted. But Cherian JV et al showed no change in the site specificities of the carcinoma of the stomach in south Indian population.…”
Section: Resultsmentioning
confidence: 99%
“…Helicobacter Pylori has been implicated in the pathogenesis of both gastric carcinoma and gastric lymphoma. 1 …”
mentioning
confidence: 99%